Limites e possibilidades de uma proposta de gestão coletiva: cursinho popular da UNESP-Franca - Carvalho, Vitor Hugo Costa [UNESP] (2014)
The current research aims to gauge the boundaries and possibilities of the existing relation between the popular preparatory course (preps) from UNESP UNIVERSITY in Franca – SP, Brazil – Faculdade de Ciências Humanas e Sociais Unesp, Franca (University Extension Program – Serviço de Extensão Universitária – SEU) and the collective self-management proposal. For such reason, we aimed to recapture the aforementioned concept using the anarchist proposal as theoretical basis, recovering the main concepts of the libertarian pedagogy aiming to build an ideal standard that will serve as a comparator for the other attempts to put self-management into practice. Firstly, from the established pattern, we will point out examples of six educational institutions which, even with completely distinct conditions, make usage of the self-management in its boundaries and possibilities, facing contradictions and showing points of detachment concerning the anarchist proposal, which will be highlighted as well as the attachment points. Secondly, after a brief explanation that involves the moment of creation and expansion of the private and alternative preparatory courses in Brazil, the preparatory course from Franca, SP will be widely explained, in order to allow people to know the greatest profusion of details concerning the whole history and activities performed by such course. The idea is that, through such information, it is possible to create explanatory categories that might evince the mechanisms used by the members of the University Extension Program to allow the students to experience democratic experiments that might attach or detach from the libertarian proposal